Strategi Komunikasi Pemasaran Biro Perjalanan Wisata Pasca Pandemi COVID-19 - Dewi, Nanda Rachma; Alamiyah, Syifa Syarifah (Peneliti.net, 2024)
The Travel Bureau business is one of the businesses affected by the COVID-19 pandemic due to regulations that limit people's activities to gather. In an effort to deal with the pandemic, a marketing communication strategy is needed, one of which is JawaXplore. Analyzed using the SOSTAC theory (Situation, Objectives, Strategy, Tactic, Action, Control), this research aims to find out what kind of marketing communication strategy JawaXplore is doing in facing the COVID-19 pandemic. This research uses descriptive qualitative methodology. The purpose of the strategy created is a stable position and avoid losses, and also foster trust in potential clients. Marketing communication activities through the @jawaxplore Instagram account are carried out by utilizing various existing features, such as uploading photos and videos on feeds, instagram stories, instagram story highlights, reels, IG TV, IG Ads, and insight.